Effect of Pyrazosulfuron-Methyl on the Photosynthetic Characteristics and Antioxidant Systems of Foxtail Millet - Ma, Ke; Zhang, Weili; Zhang, Liguang; He, Xiaoyong; Fan, Yu; Alam, Sher; Yuan, Xiangyang (Frontiers in Plant Science, 2021)
Foxtail millet (Setaria Italica L.) plays a principal role in food security in Africa and Asia, but it is sensitive to a variety of herbicides. This study was performed to clarify whether pyrazosulfuron-methyl can be used in foxtail millet fields and the effect of pyrazosulfuron-methyl on the photosynthetic performance of foxtail millet. Two foxtail millet varieties (Jingu 21 and Zhangzagu 10) were conducted using five doses (0, 15, 30, 60 and 120 g ai ha-1) of pyrazosulfuron-methyl in pot and field experiments. The plant height, leaf area, stem diameter, photosynthetic pigment contents, gas exchange parameters, chlorophyll fluorescence parameters, antioxidant enzyme activities and antioxidant contents at 7 and 15 days after pyrazosulfuron-methyl application and the yield of foxtail millet were measured. The results suggested that pyrazosulfuron-methyl inhibited the growth of foxtail millet and reduced the photosynthetic pigment contents, photosynthetic rate and photosynthetic system II activity. At the same time, pyrazosulfuron-methyl decreased antioxidant enzyme activities and antioxidant contents. Our results also indicated that the toxicity of pyrazosulfuron-methyl to foxtail millet decreased gradually with the extension of time after application. However, the foxtail millet yield was still significantly reduced. Therefore, pyrazosulfuron-methyl is not recommended for application in foxtail millet fields.